PERANCANGAN INSTALASI TATA UDARA RUANG BERSIH AREA PENIMBANGAN PADA INDUSTRI FARMASI KELAS E - Saputra, Rudi; Abdunnaser, Abdunnaser (Bina Teknika, 2018)
Cleanroom in the pharmaceutical industry is needed to eliminate a wide range of contamination, due to the room around the building materials, machinery equipment production, human and others generate millions of particles that can interfere with the quality of manufactured drugs. Cleanroom in the pharmaceutical industry is based on the ISO 14644-1 standard that is in a class of E (100.000), which can be interpreted very clean conditioned room to awake from particles and microbial contamination. The number of particles in the E (100.000) class at the size of 0,5 µm limited number of 3520000 particles/m3 were obtained from the results of the design of 446771,3769 particles/m3, for a particle size of 5 µm particle number 29000 particles/m3 is obtained by 47760,7813 partikel /m3. Raw material weighing room temperature in the desain room 21 ºC and 40% RH, and the outside temperature is 32,72 ºC and 72,77% RH. The results obtained design cooling load is 17329,077 Watt, with velocity distribution of air in the airway of 0,118 m/s in air requirement of 99,615 l/s, so that the requirements for class E (100.000) according to ISO 14644-1 to the mixed flow of air velocity.